Institutional Role in Gunung Walat Educational Forest Policy: Discourse and Historical Approaches - Yulius Hero; Rudi C Tarumingkeng; Dudung Darusman; Hariadi Kartodihardjo (Institut Pertanian Bogor (IPB University), 2012)
Institutional science with various approaches have been used in analysing forest policy at international level and in Indonesia. This research used institutional science with discourse and historical approach for the policy of Forest Territory with Special Purpose (Kawasan Hutan dengan Tujuan Khusus, KHDTK). This research study the KHDTK case of Gunung Walat Educational Forest (Hutan Pendidikan Gunung Walat, HPGW). The goal of this research is to understand discourse/narration of policy and describe the policy space for HPGW and KHDTK. Institutional analysis in this research used discourse and historical approach. Discourse analysis used IDS model supported with Wittmer-Birner model and Eden-Ackermann diagram. On the other hand, historical approach used the historical relationship. The research outcome showed that the process of creating HPGW policy is not linear, but being affected by policy discourse/narration in the process of creating HPGW policy. Faculty of Forestry IPB has been successfully managing HPGW because of the success to build policy discourse/narration which is supported by the knowledge of HPGW managers, cooperation network, and interest and power. Meanwhile, external party perceived and believed the importance of HPGW management for forestry education. The success key of HPGW policy is in structuring the institution that control the behavior of HPGW managers, so the managers obtained trust from third parties to create interest alliances which can boost HPGW management performance. HPGW policy can be used to fulfill KHDTK policy space according to Article 8, Forestry Law Number 41 Year 1999.